PENGARUH KEGIATAN BERCERITA MENGGUNAKAN MEDIA BIG BOOK TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 4-5 TAHUN DI TK TELKOM MAKASSAR - Purnama Sari, Wulan; Rusmayadi; Herlina; Fadhilah Afifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The research aims to determine the effect of storytelling activities using Big Book media on the listening abilities of children aged 4-5 years at Telkom Makassar Kindergarten. The research approach used is a quantitative approach with a Quasi Experimental Design research type. The population in the study was Telkom Kindergarten students totaling 30 children. Sampling in this research used purposive sampling. The sample in this study consisted of 20 children divided into 10 control groups and 10 experimental groups, and the data analysis techniques used were descriptive statistical analysis and non-parametric statistical analysis. Based on the research results, it can be concluded that the listening ability of children using big book media in the experimental group was better than the control group. The results of the analysis showed an average increase in the experimental group of 20.90%, while in the control group it was 13.70% and the test results showed a sig. (2-tailed) 0.06 < 0.05, then Ho is rejected and Hₗ is accepted. So, big book media has a significant influence on the listening ability of children aged 4-5 years at Telkom Makassar Kindergarten.